THU0173 Supervised physical exercise improves endothelial function and increase endothelial progenitor cells number in patients with systemic lupus erythematosus. (23rd January 2014) - Reis Neto, E.T.; Silva, A.E.; Camargo, L.M.; Semedo, P.; Pinheiro, M.M.; Silva, N.P.; Sato, E.I.
Abstract : Background: Cardiovascular disease (CVD) is an important cause of morbidity and mortality in systemic lupus erythematosus (SLE) and disturbances in endothelial function (EF) are implicated in its pathogenesis (1, 2). EF also depends on endothelial progenitor cells (EPCs) that enhance angiogenesis, promote vascular repair and have potential as a marker of CVD (3, 4, 5). SLE patients have endothelial dysfunction and fewer EPCs (6, 7). Objectives: To evaluate the effect of supervised physical exercise (SPE) on quality of life, exercise tolerance, body composition, endothelial function, EPCs number and on vascular endothelial growth factor (VEGF) level in SLE patients. Methods: Prospective, controlled, nonrandomized study. Women with SLE were allocated according to availability to participate in exercise group (EG) or control group (CG). Intervention: SPE was performed for 1 hour, 3X/week, for 16 weeks. Patients were evaluated at baseline (T0) and after 16 weeks (T16): exercise tolerance by cardiopulmonary exercise test; quality of life by SF-36; body composition by DEXA; high-resolution ultrasound of brachial artery in resting conditions, after reactive hyperaemia (flow-mediated dilation-FMD) and after oral glyceryl trinitrate (GTMD) was performed to assess endothelial function; EPCs were evaluated by flow cytometry using anti-CD34 (FITC), anti-CD133 (PE) and anti-KDR (APC); and VEGF was assessed by ELISA (R&D Systems, Minneapolis, USA). Results: 535 SLE patients were invited, 239 manifested interest, but 127 were excluded due to exclusion criteria. 55 patients dropped out due to personal reasons. Twenty four patients completed the evaluations (mean age 33.2±8.2 years and mean disease duration of 99±77.9 months). Thirteen patients were assigned in the EG and eleven in the CG. Both groups were comparable and homogeneous regarding demographic variables and cardiovascular traditional risk factors. After 16 weeks, we observed a significant increase in FMD (7.7±7.2% vs 16.9±8.8%, p=0.005) in EG without changes in the GC (4.1±4.4% vs 7.4±5.7%, p=0.62). In the EG, we also found a significant improvement in exercise tolerance (12±2.1min vs 13.5±2min, p=0.021), maximum speed (7.6±1km/h vs 8.3±1km/h, p=0.049), threshold speed (5.5±0.6km/h vs 5.9±0.6km/h, p=0.012), functional capacity (66.2±23.8 vs 82.1±11.6, p=0.035) and vitality (72.9±31.4 vs 78.8±19.7, p=0.007). EPCs were analyzed in 10 patients of the EG and in seven of the CG. We observed a significant increase in number of CD34/CD133/KDR positive cells at T16 in the EG (0.38±0.37 vs. 1.57±1.38, p=0.005), with no difference in the CG (0.62±0.83 vs. 0.82±0.58, p=0.176). There was no difference on body composition and VEGF levels in both groups comparing T0 and T16. Conclusions: Despite the small sample, this is the first study demonstrating that SPE can improve EF and EPCs number in SLE patients. The higher number of EPCs may be one of the mechanisms associated with EF improvement after an exercise program. Physical exercise can be a useful strategy to prevent CVD morbidity and mortality in SLE patients. References: Kao et al. Curr Opin Rheumatol. 2003. Pearson JD. Lupus. 2000. Asahara et al. Science. 1997. Hill et al. N Engl J Med. 2003. Werner et al. N Engl J Med. 2005. Lima et al. J Rheumatol. 2002. Westerweel et al. Ann Rheum Dis. 2007. Disclosure of Interest: None Declared